Development of Co-doped MnFe2O4 nanoparticles for electrochemical supercapacitors. Issue 7 (1st April 2021) - Deshmukh, V.V.; Nagaswarupa, H.P.; Raghavendra, N.
Abstract: Transition metal ferrites are the essential components utilized in the latest modern-day technology and these include greater elements whose oxidation states and ionic radii are important for exploring their magnetic, optical, structural, and electrochemical properties. The present investigation was targeted on the preparation, physical and electrochemical characterizations of Co-doped MnFe2 O4 nanomaterials such as 2 wt% Co-doped MnFe2 O4, 4 Wt.% Co-doped MnFe2 O4, and 8 Wt.% Co-doped MnFe2 O4 . More specifically, the study will focus on the techniques which have been employed to raise the specific capacitance of the metal oxides. Electrochemical properties such as cyclic voltammetry (CV), potentiostatic and impedance were used to analyse the super capacitive performance of Co-doped MnFe2 O4 electrodes. Based on the outcomes, it is determined that 2 wt% of Co-doped MnFe2 O4 has higher super capacitive behaviour than different samples. Precise capacitance for this nanocomposite from GCD was determined to be 551.39 F/g at a current density of 1 mA/cm 2 . Accordingly, Co-doped MnFe2 O4 may be utilized as a promising electrode for energy storage applications. It could be believed that this form of composites indicates excellent capability as electrochemical supercapacitors. Graphical abstract: Image 1